The Influence of Mindfulness on Student Learning Interests at Higher Education Institutions - Rapiadi, Rapiadi; Gautama, Sidartha Adi; Burmansah, Burmansah; Sutawan, Komang; Susanto, Susanto (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2023)
This research aims to measure mindfulness's impact on students' learning motivation in Buddhist College. Learning motivation sometimes becomes a problem in a learning society. So it needs a solution to students do not lose their motivation anymore. The researcher tries to investigate how the role of mindfulness in teaching-learning. The method that the researcher applied was a survey method with a quantitative approach. The sampling technique of this study was proportional random sampling, and the questionnaires were distributed randomly. The number of statements in the questionnaire was 74 items distributed to 71 respondents with a measurement scale of questionnaire answers using a Likert scale. The results of hypothesis testing and simple linear regression obtained a t arithmetic value of 24,322 with a significant level of 0.000, while ttable with n = 71 and = 0.05 got a value of 1.667. It can be assumed that t arithmetic ttable (24,322 > 1.667) or sig < 0.05 (0.000 0.05), then Ha is accepted while H0 is rejected. While the value of R Square in this study is 0.896, meaning that mindfulness affects interest in learning by 89.6%. With the results of the data analysis, it is concluded that there is an Influence of Mindfulness on Student Interest in the Jinarakkhita School of Buddhism, Bandar Lampung, in 2021. The magnitude of the influence is 89.6%, while other factors influence 10.4%.